Determinan Pemilihan Implan Pada Pasangan Usia Subur Di Kecamatan Medan Petisah - Rahmi, Ayu Amalia; Hadi, Ella Nurlaella (UI Scholars Hub, 2020)
Background. Indonesia's population has increased from 265,015.3 million in 2018 to 268,074.6 million in 2019. The government has created a program to intervene in the problem of uncontrolled population growth, namely the family planning (KB) program which is promoted and effective is the Long-Term Contraception Method (MKJP) with implants is one of the superior contraceptives of the BKKBN. Objective. This study aimed to to see the selection of implants and their determinations. Method. This study used a quantitative study with cross sectional analytic survey method. Sample of 85 acceptors from 560 were selected using simple random sampling. Data collection was carried out through interviews using a questionnaire. Data were analyzed by univariate and bivariate using chi-square test. Results. Study found 11.8% of respondents used the implant method. 71.8% respondents have less knowledge, 65.9% of respondents have a negative attitude, 83.5% of respondents think that the role of health workers is still lacking, and 67.1% of respondents did not get support from their husbands. The results of the bivariate analysis showed that there was a relationship between knowledge, the role of health workers, and husband's support with the choice of implant contraception, while attitudes showed no relationship with the choice of implant contraception. Conclusion. Knowledge variables, the role of health workers, and husband's support was related with the choice of implants in respondents.